2019 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--32630
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Conceptual Framework to Understand Student Participation in Entrepreneurship Education Programs

Abstract: Aileen is faculty in Engineering Education and Biomedical Engineering. Previously, Aileen was the Associate Director for Academics in the Center for Entrepreneurship and was responsible for building the Program in Entrepreneurship for UM undergraduates, co-developing the masters level entrepreneurship program, and launching the biomedical engineering graduate design program. Aileen has received a number of awards for her teaching, including the Thomas M. Sawyer, Jr. Teaching Award, the UM ASEE Outstanding Prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…In this study, we use an adaptation of Cross's Chain-of-Response (COR) model of participation in adult learning (Cross, 1981), specific to entrepreneurship education, as our conceptual framework (Shekhar et al, 2018). Exploration of participation in EEPs in the context of adult learning theory is critical, as adult participation theory acknowledges a developmental difference in adult learning (Abdullah et al, 2008;Neck & Corbett, 2018).…”
Section: Background and Conceptual Frameworkmentioning
confidence: 99%
See 4 more Smart Citations
“…In this study, we use an adaptation of Cross's Chain-of-Response (COR) model of participation in adult learning (Cross, 1981), specific to entrepreneurship education, as our conceptual framework (Shekhar et al, 2018). Exploration of participation in EEPs in the context of adult learning theory is critical, as adult participation theory acknowledges a developmental difference in adult learning (Abdullah et al, 2008;Neck & Corbett, 2018).…”
Section: Background and Conceptual Frameworkmentioning
confidence: 99%
“…1). The three most commonly used overarching theories used in entrepreneurship education research identified through a systematic literature review of 359 empirical studies (Shekhar et al, 2018) are the Theory of Planned Behavior (TPB, Azjen & Ajzen, 1991), Shapero's Entrepreneurial Event Theory (SEE, Shapero & Sokol, 1982, and Social Cognitive Career Theory (SCCT, Bandura, 1986). These three theories primarily address individual behavior in different contexts and identify antecedents to behavior which are similar to those noted in the COR model.…”
Section: Background and Conceptual Frameworkmentioning
confidence: 99%
See 3 more Smart Citations